Carving a Space for Elite Republicanism: Hierarchy, Deference and Paternalism in American Political Development - O'Hara, Jonathan (Europolis, Journal Of Political Science And Theory, 2010)
The present article is a review of the American Political Development literature dealing with the issue of national administrative politics and development in late nineteenth century American history. Particular attention is paid to the ways in which historical institutionalists discount the importance of elite republican ideology as an explanation of national administrative growth. Attention is also paid to the ways in which sociological institutionalists view republicanism as a viable ideological alternative only for far flung and marginalized social interest groups. The article argues for studying the ideology also in terms of its elitist tradition and the tradition’s application to national administrative politics and development in the American context, emphasizing categories of hierarchy, deference and paternalism. As a review of seminal works related to the research program of American Political Development, this article is of particular use to those studying American development at the turn of the twentieth century.
Keywords: American politics; United States; dept.psc; elitism; ideology; republicanism

Unique Policymaking in Action: The District Council and the Legislative Process - Wharton, Jonathan L. (Law, Politics, and African Americans in Washington, DC, 2010)
Law, Politics, and African Americans in Washington, DC explores the legal challenges and triumphs of African Americans and law and politics in Washington, DC, a city whose majority population comprises African Americans. It examines the interconnection between law and politics in Washington, DC, because it is vital to know the legal conditions under which the African American residents of the most powerful city in the world live, based on sound empirical evidence. Law, Politics, and African Americans in Washington, DC addresses two major questions: - Why study African Americans in terms of law and politics? - Why examine law and politics at the local level, in this case Washington, DC?
Keywords: dept.pch

The Colonels' coup and the American embassy: A Diplomat's view of the breakdown of democracy in cold war Greece - Keeley, R.V.; Iatrides, J.O. (Penn State University Press, 2010)
The so-called Colonels' coup of April 21, 1967, was a major event in the history of the Cold War, ushering in a seven-year period of military rule in Greece. In the wake of the coup, some eight thousand people affiliated with the Communist Party were rounded up, and Greece became yet another country where the fear of Communism led the United States into alliance with a repressive right-wing authoritarian regime. In military coups in some other countries, it is known that the CIA and other agencies of the U.S. government played an active role in encouraging and facilitating the takeover. The Colonels' coup, however, came as a surprise to the United States (which was expecting a Generals' coup instead). Yet the U.S. government accepted it after the fact, despite internal disputes within policymaking circles about the wisdom of accommodating the upstart Papadopoulos regime. Among the dissenters was Robert Keeley, then serving in the U.S. Embassy in Greece. This is his insider's account of how U.S. policy was formulated, debated, and implemented during the critical years 1966 to 1969 in Greek-U.S. relations. © 2010 Robert V. Keeley All rights reserved.
Journal Abbreviation: The Colonels' Coup and the Amer. Embassy: A Diplomat's View of the Breakdown of Democr. in Cold War Greece Pages: 274 Publication Title: The Colonels' Coup and the Amer. Embassy: A Diplomat's View of the Breakdown of Democr. in Cold War Greece
Keywords: dept.psc